2011
DOI: 10.1007/s10753-011-9326-4
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Inflammatory Activation in Subjects with Acute Coronary Syndrome and Left Ventricular Dysfunction

Abstract: Several lines of evidence indicate that increased inflammatory cytokine levels can be used for risk prediction in patients with acute coronary syndrome (ACS). This study therefore aimed to evaluate correlations between levels of soluble interleukin (IL)-2 receptor (sIL-2r), IL-6, and IL-8 and in-hospital incidence of acute heart failure (AHF) and left ventricular (LV) systolic dysfunction in the subacute phase of ACS. In 48 consecutive patients with ACS, circulating levels of sIL-2r, IL-6, and IL-8 were ascert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
0
21
0
2
Order By: Relevance
“…On the other hand, one meta analysis study reviewed twelve studies and the authors concluded that sIL-2R is not a useful inflammatory marker of coronary artery calcification (13). In (14). This study demonstrates such findings but in asymptomatic patients and in absence of acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…On the other hand, one meta analysis study reviewed twelve studies and the authors concluded that sIL-2R is not a useful inflammatory marker of coronary artery calcification (13). In (14). This study demonstrates such findings but in asymptomatic patients and in absence of acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 60%
“…In heart failure of whatever cause, serum sIL-2R level is high before treatment, and then reduced after using therapeutic agents with pleiotropic effects like statins (7). Recent study shows that sIL-2R level is high in patients with acute coronary syndrome in presence of systolic dysfunction or acute heart failure, and the levels of sIL-2R were proportional to left ventricle end-diastolic diameter and endsystolic diameter (8). Cardiometabolic risk factors as well as abnormal ventricular function often exited in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [5]- [7] have shown that IL6 and other pro-inflammatory cytokines were significantly increased in patients with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…When plaque has inflammation or rupturing, the blood concentrations of IL-6 tend to increase. IL-6 and other cytokines were significantly increased in ACS patients (De Gennaro et al, 2012). Lai et al (2011) also found that serum IL-6 levels of plaque in ACS patients were significantly higher than those of the control group, while IL-6 levels of the unstable and mixed plaque group were also significantly higher than the control group.…”
Section: Introductionmentioning
confidence: 94%